Synthesis, Structure, and Function of PCP Pincer Transition-Metal-Complex-Bound Norvaline Derivatives - Takaya, Hikaru; Iwaya, Takashi; Ogata, Kazuki; Isozaki, Katsuhiro; Yokoi, Tomoya; Yoshida, Ryota; Yasuda, Nobuhiro; Seike, Hirofumi; Takenaka, Toshio; Nakamura, Masaharu (Synlett, 2013)
A PCP pincer palladium-complex-bound norvaline, Boc-l-[Pd]Nva-OMe, was synthesized and fully characterized by NMR, FT-ICR-MS, and X-ray crystallography. Selective N- and C-terminus transformations of Boc-l-[Pd]Nva-OMe were performed by conventional deprotection–condensation procedures to afford lipophilic palladium-bound norvaline derivatives without metal detachment. The N-/C-bisfunctionalized palladium-bound norvaline showed self-assembly properties, as evidenced by supramolecular gel formation. The catalytic activity of the supramolecular gel was assessed in the 1,4-conjugate addition of phenylboronic acid.
Keywords: amino acids; cross-coupling; catalysis; palladium; self-assembly